The Medicaid Tape-to-Tape Project: Empirical Use of a Uniform Data Base - Pine, Penelope L. (1985)
This project is acquiring person-level data on Medicaid enrollment, claims and providers from five State Medicaid Management Informations Systems, California, Georgia, Michigan, New York, and Tennessee. These data will be used to create uniform files, provide descriptive reports, support analysis and evaluation and develop methodology for on-line data base management. This project provides 5 years, 1980-1984 of uniform Medicaid data for the conduct of analysis of program management, evaluation of policy alternatives, and feedback to the States in the area of Medicaid financing.